2012
DOI: 10.1186/1475-2840-11-77
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic syndrome and progression of carotid atherosclerosis over 13 years. The Tromsø study

Abstract: BackgroundThe metabolic syndrome (MetS) is associated with increased risk of cardiovascular disease. In this study, we examine if metabolic syndrome predicts progression of atherosclerosis over 13 years.MethodsParticipants were 1442 men and 1532 women in the population-based Tromsø Study who underwent carotid ultrasound examinations at baseline in the 4th (1994–5) and at follow-up in the 6th survey (2007–8). Of these, 278 men and 273 women fulfilled the criteria for the MetS, defined according to a modified ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 28 publications
10
51
1
1
Order By: Relevance
“…In other words, MetS predicted the occurrence of new carotid plaque and may be correlated with changes in IMT over time. These results are consistent with the findings of several longitudinal 15,16,23,24) and cross-sectional studies 14,25,26) that addressed the relationships between MetS, carotid plaque and C-IMT. In the present study, the presence of carotid plaque was associated with accelerated C-IMT changes (Cont Table 1 stress and proinflammatory signaling in the vessel wall 38) .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In other words, MetS predicted the occurrence of new carotid plaque and may be correlated with changes in IMT over time. These results are consistent with the findings of several longitudinal 15,16,23,24) and cross-sectional studies 14,25,26) that addressed the relationships between MetS, carotid plaque and C-IMT. In the present study, the presence of carotid plaque was associated with accelerated C-IMT changes (Cont Table 1 stress and proinflammatory signaling in the vessel wall 38) .…”
Section: Discussionsupporting
confidence: 90%
“…MetS is also associated with early carotid atherosclerosis 13,14) . Several prospective studies have shown that MetS is associated with the progression of atherosclerosis 15,16) . These studies highlight the importance of MetS in the atherosclerotic process.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertriglyceridemia, as one of the components of the MS, is closely related to a constellation of metabolic risk factors including a central distribution of adiposity or visceral obesity, insulin resistance, impaired glucose tolerance, hypertension, and high TG and/or low HDL-C, associated with an atherogenic, procoagulant, and proinflammatory state [56][57][58][59][60][61][62][63][64].…”
Section: Hypertriglyceridemia As a Major Component Of Atherogenic Dysmentioning
confidence: 99%
“…Analyzing the progression of carotid atherosclerosis, it should be stressed that subjects with MS have higher levels of intima-media thickness (IMT) and total plaque area at follow up than those without MS. MS predicts progression of IMT in individuals below 50 years of age, but not in older age groups, suggesting thus that MS may be involved in the initial steps of the atherosclerotic process [31].…”
Section: Prosmentioning
confidence: 97%